2018
DOI: 10.1029/2017wr022421
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying and Mitigating Wind‐Induced Undercatch in Rainfall Measurements

Abstract: Despite the apparent simplicity, it is notoriously difficult to measure rainfall accurately because of the challenging environment within which it is measured. Systematic bias caused by wind is inherent in rainfall measurement and introduces an inconvenient unknown into hydrological science that is generally ignored. This paper examines the role of rain gauge shape and mounting height on catch efficiency (CE), where CE is defined as the ratio between nonreference and reference rainfall measurements. Using a pi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
91
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 123 publications
(101 citation statements)
references
References 38 publications
(49 reference statements)
2
91
1
Order By: Relevance
“…For example, analysing some experimental observations in the field, Yang et al [27] considered that the impact of wind speed on the measurements of rain gauges can be negligible. But some other researchers found that the wind could induce undercatch of rain gauges [28,29]. Our evaluation result cannot support this viewpoint probably due to the relatively small wind speed (less than 5 m/s) observed during the experiments.…”
Section: Impact Of Wind Speed and Rainfall Intensity On Rg3-m Measurecontrasting
confidence: 75%
“…For example, analysing some experimental observations in the field, Yang et al [27] considered that the impact of wind speed on the measurements of rain gauges can be negligible. But some other researchers found that the wind could induce undercatch of rain gauges [28,29]. Our evaluation result cannot support this viewpoint probably due to the relatively small wind speed (less than 5 m/s) observed during the experiments.…”
Section: Impact Of Wind Speed and Rainfall Intensity On Rg3-m Measurecontrasting
confidence: 75%
“…The turbulent kinetic energy, k , provides an indication of the level of turbulence generated by the rain gauge shape. Using real‐world boundary conditions (Pollock et al, ) retains the wind speed characteristics that are enforced on the system in the field. These can be nonparameterized and scaled according to each input wind speed selected.…”
Section: Simulation Resultsmentioning
confidence: 99%
“…p = 0 m 2 s −2 (where the pressure units are normalized with the air density). Turbulent kinetic energy . Calculated as k=3/2(IUw)2 with U w the undisturbed wind speed and I = 0.20 the turbulent intensity evaluated from field measurements (Pollock et al, ). Three‐dimensional wind measurements have been obtained using a Gill WindMaster ultrasonic anemometer at a resolution of 20 Hz.…”
Section: Methods Of Investigationmentioning
confidence: 99%
“…CC BY 4.0 License. or more in conditions of extremely heavy rainfall rates over 50-100 mmh −1 (Nystuen, 1999;Sieck et al, 2007;Pollock et al, 2018).…”
Section: Introductionmentioning
confidence: 99%